2015
DOI: 10.1136/gutjnl-2014-308971
|View full text |Cite
|
Sign up to set email alerts
|

Host cell mTORC1 is required for HCV RNA replication

Abstract: ObjectiveChronically HCV-infected orthotopic liver transplantation (OLT) recipients appear to have improved outcomes when their immunosuppressive regimen includes a mammalian target of rapamycin (mTOR) inhibitor. The mechanism underlying this observation is unknown.DesignWe used virological assays to investigate mTOR signalling on the HCV replication cycle. Furthermore, we analysed HCV RNA levels of 42 HCV-positive transplanted patients treated with an mTOR inhibitor as part of their immunosuppressive regimen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 39 publications
3
42
0
Order By: Relevance
“…Furthermore, such inactivation and the downstream inhibition of the PI3/Akt/mTOR pathway resulted in HCV-induced autophagy (14), which may contribute to membrane rearrangements to accommodate replication complexes (15,16). Similar results have been recently observed using mTOR inhibitors (17). How the transition of Akt/PKB from an early-activated plasma membrane-bound form to a cytoplasm location takes place is not known.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Furthermore, such inactivation and the downstream inhibition of the PI3/Akt/mTOR pathway resulted in HCV-induced autophagy (14), which may contribute to membrane rearrangements to accommodate replication complexes (15,16). Similar results have been recently observed using mTOR inhibitors (17). How the transition of Akt/PKB from an early-activated plasma membrane-bound form to a cytoplasm location takes place is not known.…”
supporting
confidence: 67%
“…A deeper knowledge of the NS5B-Akt/PKB molecular interaction could be used to design small-molecule inhibitors directed to interfere with this critical connection, by analogy to the proposed new Bcl-2 inhibitors for cancer treatment (46). Furthermore, Akt/PKB inhibitors currently undergoing clinical trials could be useful for HCV infection treatment, as it has been recently showed for those inhibiting mTORC1 (17). Taken together, these results highlight the importance of the PI3K/Akt/mTOR pathway in HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…mTORC2 contains mTOR, GβL, and rictor and directly phosphorylates the prosurvival kinase Akt/PKB, but its cellular function is just beginning to be understood (37). Recently, Stöhr et al (38) reported that the host cell mTORC1/raptor is required for HCV replication, rather than suppression of HCV replication. To clarify the seemingly contradictory roles of mTOR in their and our studies, we dissected the antiviral effects of raptor (mTORC1) and rictor (mTORC2) downstream of DAPK.…”
Section: Discussionmentioning
confidence: 99%
“…Whichever the cause, it is remarkable that in both cases, HCV infection did not recurred despite the start and maintenance of immunosuppressive therapy. On the other hand, although recent report suggested a possible role of mTOR in favouring viral decay [7], this issue remains controversial based on a thorough review of the current literature.…”
Section: Discussionmentioning
confidence: 99%